Analisis Rasio Keuangan terhadap Kinera Keuangan pada Bank Perkreditan Rakyat di Kota Batam - Debora, Devi Pascha; Tipa, Handra (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Rural Banks are a financial institution that plays a role in the community's economy by collecting excess funds from the public and lending them to people who need funds. Every company, both bank and non-bank, reports at a certain time the company's financial performance in the form of annual financial reports. Financial statements show the financial performance of a company in running its business, what are the weaknesses and strengths of the company. The company's financial performance is a representation of the company's financial position over a certain period of time. Banks with good financial performance can create a good Indonesian economy and help improve the standard of living of the Indonesian people. This study aims to analyze and determine the effect of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA). This study uses secondary data obtained from the website of the Financial Services Authority, with a sampling technique using purposive sampling, namely the sampling technique by selecting data sources based on criteria and based on certain considerations so that a total sample is obtained 135. The data analysis technique used is descriptive analysis, classical assumption test (normality, multicollinearity, heteroscedasticity and autocorrelation), multiple linear regression analysis and hypothesis testing (partial, simultaneous and coefficient of determination). The results of this study indicate that partially Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a significant effect on Return On Assets (ROA), while the Non Performing Loan (NPL) have no significant effect on Return On Assets (ROA). Furthermore, it is known that simultaneously the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) have a significant effect on Return On Assets (ROA). Keywords: Capital Adequacy Ratio (CAR); Non Performing Loan (NPL); Loan to Deposit Ratio (LDR); Return On Assets (ROA).